Attenuated Listeria monocytogenes: a powerful and versatile vector for the future of tumor immunotherapy - Wood, Laurence M.; Paterson, Yvonne (Frontiers in Cellular and Infection Microbiology, 2014)
For over a century, inactivated or attenuated bacteria have been employed in the clinic as immunotherapies to treat cancer, starting with the Coley's vaccines in the 19th century and leading to the currently approved bacillus Calmette-Guérin vaccine for bladder cancer. While effective, the inflammation induced by these therapies is transient and not designed to induce long-lasting tumor-specific cytolytic T lymphocyte (CTL) responses that have proven so adept at eradicating tumors. Therefore, in order to maintain the benefits of bacteria-induced acute inflammation but gain long-lasting anti-tumor immunity, many groups have constructed recombinant bacteria expressing tumor-associated antigens (TAAs) for the purpose of activating tumor-specific CTLs. One bacterium has proven particularly adept at inducing powerful anti-tumor immunity, Listeria monocytogenes (Lm). Lm is a gram-positive bacterium that selectively infects antigen-presenting cells wherein it is able to efficiently deliver tumor antigens to both the MHC Class I and II antigen presentation pathways for activation of tumor-targeting CTL-mediated immunity. Lm is a versatile bacterial vector as evidenced by its ability to induce therapeutic immunity against a wide-array of TAAs and specifically infect and kill tumor cells directly. It is for these reasons, among others, that Lm-based immunotherapies have delivered impressive therapeutic efficacy in preclinical models of cancer for two decades and are now showing promise clinically. In this review, we will provide an overview of the history leading up to the development of current Lm-based immunotherapies, the advantages and mechanisms of Lm as a therapeutic vaccine vector, the preclinical experience with Lm-based immunotherapies targeting a number of malignancies, and the recent findings from clinical trials along with concluding remarks on the future of Lm-based tumor immunotherapies.